'The Implementation of the Directive on Copyright and Related Rights in the Digital Single Market' ‒ Conference Report on the Sixth Binational Seminar of the Technische Universität Dresden and Charles University in Prague, 1 December 2020. Issue 8 (5th June 2021) - Linke, David; Žikovská, Petra
Abstract: 'It's drafting time!', but we are not talking about Patrick Mahomes, Alexis Lafrenière or Stephen Curry, 1 rather about the implementation proposals for the Digital Single Market (DSM) Directive. This Directive caused a certain media stir in the run-up to it, and now the national legislatures need to implement the provisions of the Directive into the respective national laws. The Member States have until June 2021 to make the relevant transpositions. It will become apparent that very different approaches are being pursued in this respect, but that there are also similarities. For that reason, the sixth binational seminar has taken this as an opportunity to examine on 1 December 2020 the implementation efforts made by Germany and the Czech Republic in a comparative legal analysis under the topic: 'The Implementation of the Directive on Copyright and related rights in the Digital Single Market'.